2019
DOI: 10.1002/jaba.605
|View full text |Cite
|
Sign up to set email alerts
|

Teaching children with autism spectrum disorder to tact auditory stimuli

Abstract: Studies on teaching tacts to individuals with autism spectrum disorder (ASD) have primarily focused on visual stimuli, despite published clinical recommendations to teach tacts of stimuli in other sensory domains as well. In the current study, two children with ASD were taught to tact auditory stimuli under two stimulus‐presentation arrangements: isolated (auditory stimuli presented without visual cues) and compound (auditory stimuli presented with visual cues). Results indicate that compound stimulus presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 6 publications
5
26
0
Order By: Relevance
“…et al, preference for social and non-social stimulus was assessed using portable tablet computers [32]. Hanney NM et al, claims that in teaching methodology compound (auditory stimulus presented with visual cues) stimulus presentation was more effective than isolated (auditory stimulus presented without visual cues) [33]. The robot-child interaction allows the children with ASD to improve communication skills as the environment is highly predictable rather than a complex traditional one [34].…”
Section: Introductionmentioning
confidence: 99%
“…et al, preference for social and non-social stimulus was assessed using portable tablet computers [32]. Hanney NM et al, claims that in teaching methodology compound (auditory stimulus presented with visual cues) stimulus presentation was more effective than isolated (auditory stimulus presented without visual cues) [33]. The robot-child interaction allows the children with ASD to improve communication skills as the environment is highly predictable rather than a complex traditional one [34].…”
Section: Introductionmentioning
confidence: 99%
“…As such, we calculated effect sizes for 25 single-case and two group design studies. For studies that conducted a comparison (e.g., Hanney et al., 2019; sound-only condition compared to an object-with-sound-compound condition), we calculated the effect sizes for all conditions and reported them separately. Table 3 shows whether a study included in this review has either met, met with reservations, or has not met quality standards for research; their effects sizes; and the total number of AB comparisons within each study for single-case design studies.…”
Section: Resultsmentioning
confidence: 99%
“…The current review yielded a few studies that specifically asked research questions about the effects of individual components. One example is Hanney et al. (2019) who compared auditory stimuli presented without visual cues (e.g., dog barking) with compound stimuli that included auditory and visual cues (e.g., a toy dog that emits barking noises) and found that compound stimuli has a higher effect size (i.e., Tau-U = 0.71) than using just the auditory stimuli (Tau-U = 0.48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Sivaraman et al (2020), some idiosyncratic modifications were necessary for participants based on observed patterns of behavior, participant-specific repertoires, or face coverings. Making modifications based on observed patterns of behavior and functional relations is common in the behavior-analytic literature (e.g., Bergmann et al, 2020;Hanney et al, 2019;Kisamore et al, 2016;Shillingsburg et al, 2014;Tiger et al, 2009;Williams et al, 2003). Although minor modifications were necessary for specific participants in the present study (e.g., change in mask type to include a nose clip, modified definition of tolerance), the primary components of the treatment package (i.e., graduated exposure, prompts, and differential reinforcement) remained constant across participants.…”
Section: Discussionmentioning
confidence: 99%